Development of a Novel Task for Investigating Insensitivity to Future Consequences: Two Studies Conducted with Undergraduates and Community Volunteers. - Ma, Xinyao; Roberts, John E. (Journal of Psychopathology & Behavioral Assessment, 2026)
We present two studies that aimed to develop and validate a novel task for investigating insensitivity to future consequences (IFC) in decision-making. The task, referred to as the Scenario Task (ST), expands the scope of IFC investigation beyond monetary outcomes and involves decision-making regarding approach versus avoidance behaviors in hypothetical scenarios. The key manipulation involves the presence versus absence of long-term consequences embedded within the scenario. Study 1 involved a focus group compromising 21 (76% female) psychology undergraduates to gather feedback and make modifications to the task. Study 2 involved an experiment with 208 (80% female) Research Match volunteer participants to examine the effectiveness of the manipulation, potential bias, and the internal consistency of the ST, as well as potential moderators, including future thinking vividness. Results indicated that the inclusion of long-term consequences significantly increased approach decisions independent of participants' age and their perceptions of scenario characteristics. These findings provide preliminary evidence for validity and reliability of the ST. Limitations of the current study and recommendations for future directions are discussed.